Afghanistan: On the Razor's Edge - Hayward, Fred (International Higher Education, 2011)
This piece focuses on the current state of higher education in Afghanistan, plans for badly needed quality improvement, measured increased access and impediments to change. On the one hand are strong demands to improve quality and on the other pressures to increase access regardless of its impact. While there is broad university support for quality improvement, lack of government and donor support for higher education poses major obstacles to change.